2004
DOI: 10.1007/s00467-004-1716-5
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin-II levels in children with minimal change nephrotic syndrome

Abstract: Human urotensin-II (hU-II) is the most potent mammalian vasoconstrictor identified to date. Although it is expressed mainly in the brain and spinal cord, it is also detected in other tissues, such as the kidney. It has been speculated that U-II might be an important physiological mediator of vascular tone and blood pressure in humans. To our knowledge, no studies have investigated the level of U-II in children with minimal change nephrotic syndrome (MCNS). Considering the renal synthesis and vasoactive role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 16 publications
3
18
0
3
Order By: Relevance
“…Previously, we investigated the level of U-II in children with MCNS, [11] and to our knowledge, there is no previous study about the possible role of U-II in other childhood glomerulonephritis. As has been demonstrated, activated components of the immune system initiate most forms of human glomerulonephritis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, we investigated the level of U-II in children with MCNS, [11] and to our knowledge, there is no previous study about the possible role of U-II in other childhood glomerulonephritis. As has been demonstrated, activated components of the immune system initiate most forms of human glomerulonephritis.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we also demonstrated that U-II was present in plasma and urine samples of children with minimal change nephrotic syndrome. [11] The purpose of present study was to determine the expression of h U-II in kidneys of children with chronic glomerular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…40 Thus, similar to other autocoids, UTN may also act as a circulating hormone. Plasma UTN is much increased in patients with renal diseases, including minimal change glomerulopathy, 41 diabetic nephropathy, 42 chronic kidney disease in general, 24 and ESRD in particular. 19,20 …”
Section: Urotensin In Renal Diseases and In Esrdmentioning
confidence: 99%
“…Moreover, patients, in relapse and in remission, had lower plasma and urine UII concentrations compared to healthy controls. Plasma UII had a strong correlation with plasma albumin, only in remission [22]. More dense UII immunoreactivity in renal biopsy specimens of children with membranoproliferative glomerulonephritis compared to healthy kidneys has been found and a possible autocrine/paracrine function of UII in kidneys has been considered [23].…”
Section: Discussionmentioning
confidence: 99%